Security dynamics in West Asia and Turkey - Edited by Liyaqat Ayub Khan (New Delhi G. B. Books, 2017)
This Is A Book That Clinically Examines Critical Security Issues In West Asia, Offers Insights And Affords Solutions And Some Policy Choices For India In A Dispassionate Manner. A Must-Read For Policy Makers, Students Researchers And Even Experts.
Keywords: Security and Foreign Affairs; Asie Mineure Relations militaires Congrès; Diplomatic relations; Middle East Foreign relations Congresses